Uma interface gráfica de usuário para projeto e implementação de filtros digitais com processador dedicado - Machado, Arnaldo Cordeiro (1996)
This work describes a software platform developed in order to support the design and DSP-based implementation of digital filters. It is a WINDOWS program designed to run on a personal computer containing a DSP board. A card based on the 16-bit fixed point Texas Instruments TMS320C25 chip is used, which is attached to the ISA PC bus. The developed software is specially designed to accomplish three main features: the filter design task, restricted to the PC microprocessor, the real-time synchronous filter algorithm, running exclusively on the DSP, and the necessary information exchanging between both processors, and between the PC computer and the user, in order either to load filter parameters or to check for the filter input/output signals. In addition, the user may edit/view text files containing the filter transfer function or network coefficients, or edit/compile/debug files that contain assembly code for the DSP.